IMPLEMENTATION OF ISLAMIC VALUE ON LEADERSHIP, ORGANIZATIONAL CULTURE AND SPIRITUALITY TO PERFORMANCE - Rizki Febriani (Universitas muhammadiyah malang, 2021)
This study aims to analyze the effect of Islamic leadership in increasing Islamic performance through Islamic organizational culture and Islamic spirituality. A total of 107 questionnaires have been distributed to the Muslim entrepreneur community in Malang, East Java, Indonesia. Data analysis using Partial Least Square. The results of this study indicate that the application of Islamic Leadership can improve the practice of Islamic Organizational Culture and this can encourage increased performance. The application of Islamic Leadership can increase Islamic Spirituality and this can encourage increased performance and the application of Islamic Leadership can increase Islamic Performance. In this research, Muslim entrepreneurs should improve their fathanah attitude and also pay attention to the application of the elements of the Islamic Organizational Culture and Islamic Spirituality.